2007
DOI: 10.1126/stke.3822007pe15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PC12 Cell Differentiation by cAMP Signaling to ERK Independent of PKA: Do All the Connections Add Up?

Abstract: Pituitary adenylate cyclase–activating polypeptide (PACAP) is a neuropeptide that elevates adenosine 3′,5′-monophosphate (cyclic AMP, also abbreviated cAMP) to elicit neuritogenesis in PC12 cells. This effect appears to be independent of cAMP-dependent protein kinase (PKA) yet dependent on cAMP, leading to the conclusion that another cAMP-binding protein and subsequent signaling pathway must exist to mediate this PKA-independent signaling mechanism. Such a protein was identified as exchange protein directly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…In most cells, PKA inhibits ERK, but it may activate ERK through small GTPase Rap-1 in the B-Rafexpressing cells. In addition, cAMP may function in a PKAindependent way through Epacs to induce ERK activation (50,62). The ERK, in our studies, was activated in both a PKA-dependent and -independent manner, as it cooperated with PKA to regulate CREB activation and cathelicidin transcription ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In most cells, PKA inhibits ERK, but it may activate ERK through small GTPase Rap-1 in the B-Rafexpressing cells. In addition, cAMP may function in a PKAindependent way through Epacs to induce ERK activation (50,62). The ERK, in our studies, was activated in both a PKA-dependent and -independent manner, as it cooperated with PKA to regulate CREB activation and cathelicidin transcription ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Besides playing a central role in neuritogenesis, ERK1 and -2, activated in response to PKC oxidative activation, protect cells from oxidants. ERK-activated p90RSK phosphorylates and activates CREB, which in turn induces the transcriptional activation of cell survival proteins that have a cAMP-response element in their promoter region (4,5). In this context, it is interesting to note that thioredoxin, a protein-disulfide reductase, has a cAMP-response element in its promoter region, and its induction plays a key role in neuroprotection (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…NGF induces neuritogenesis in PC12 cells by binding to and activating receptor-associated tyrosine kinase, TrkA (4,5,16). The associated signaling pathway leads to the activation of B-Raf (via Ras and Rap1), which is coupled to the activation of mitogen-activated protein kinase (MAPK) kinase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant PACAP target receptor in the adrenal medulla is the high affinity PAC 1 -R, a G s -linked receptor that activates adenylate cyclase to increase cyclic adenosine monophosphate (cAMP) (24,25). Recent studies have shown that PACAP stimulation activates the stimulatory exchange protein activated by cAMP (Epac) pathway through the elevation in cAMP (26,27), triggering phospholipase C and a protein kinase C (PKC)-dependent subthreshold depolarization that is necessary for catecholamine release from chromaffin cells (16). PACAP-mediated exocytosis is independent of sodium-based action potentials (28) or nicotinic acetylcholine receptor function (29,30), thus bypassing key sites of nicotinic secretory desensitization.…”
mentioning
confidence: 99%